La idea de Nación en el Facundo - D'Auría, Aníbal (2009)
This paper makes a dialectical interpretation of Sarmiento's famous\nbook, as from certain recent debates on nationalism, patriotism, and cosmopolitism. Foucault's theses (Society Must Be Defended) provide theoretical tools to understand Sarmiento's interpretation of the May Revolution and the subsequent civil war. Sarmiento develops an idea of nation as a project in the future, i.e. as a historical objective to be reached when the universal element (European civilization) and the specific element (American idiosyncrasy) finally find a "synthesis" superseding the antinomy